Analisis Kualitas Investasi Dana Pensiun Terhadap Peningkatan Pendapatan Dana Pensiun Pada PT. PUSRI Palembang (Studi Kasus Pada Yayasan Dana Pensiun Karyawan PT. PUSRI) - Masnoni; Lia Sari; Kemas Welly Angga Permana; Sri Sutandi (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2017)
This study discusses the analysis of Pension Fund Investment Quality to the Increase in Pension Fund Income, which aims to determine the level of corporate earnings more optimal. The object of this research is Yayasan Dana Pensiun Karyawan PT. Pusri Palembang which organizes a Definite Benefit Pension Program. Techniques used in this research are ratio analysises, those arefunding ratio,profitability ratio and trend analysis. While the techniques of data collection of used are field studies through observation, interviews and literature study. This indicates that the Pension Fund of PT. Pusri gain income from 2013 until 2017. However, this does not affect the level of funding quality which is still at levelIII. Instead, an increase in profits will impact on improving thequality of better financing. Suggestions that can be given by the writerto Dana Pensiun PT. Pusriare, itshould increase the amount of wealth to finance more than the amount of actuarial liabilities, the founder should reduce the deficit that occurs so that the quality of funding increases so that the income or obtained more optimal.